Primary lymphoma of anus in a patient with human immunodeficiency virus/AIDS - Ernesto Arias Beatón; Martha Beatriz Arias Beatón; Yoryana Elena Tellería León (Centro Provincial de Información de Ciencias Médicas, 2017)
The case report of a 47 years patient with the human immunodeficiency virus/AIDS for 5 years is presented. He went to the Surgery Service in the Government Hospital of Mbabane in Swaziland, due to an anus malignancy; hemorrhoids was diagnosed, but its size continued increasing, along with bleeding and acute pain.  An incision biopsy that indicated the presence of a high grade lymphoma malignancy was carried out.  Later on the patient was evaluated in the Oncology Service, where the necessary complementary exams were indicated, revealing that neoplasm was in IE stage; so  he was referred to South Africa to receive combined chemotherapy, with which the malignant lesion disappeared and the disease was controlled.